Burundi : Use of Fund Resources-Request for Post-Conflict Emergency Assistance. (IMF Staff Country Reports; Country Report ;, 2003)
This paper examines Burundi's Use of IMF Resources and a Request for Post-Conflict Emergency Assistance. Implementation of the 2002 program was broadly on track, despite constraints resulting from the delays in and earmarking of external aid disbursements. Fiscal developments were in line with the objectives set under the revised finance law approved in August. All but two of the quantitative indicators were observed, and all structural measures were implemented. The IMF staff recommends approval of the authorities' request for a second drawing under the IMF's post-conflict emergency assistance policy.